Upregulation of kappa opioid receptor system and its association with relapse to morphine/methamphetamine (poly-drug) addiction - Wasli, Nur Syafinaz; Ridzwan, Irna Elina; Azzubaidi, Marwan Saad; Kasmuri, Abdul Razak; Ahmed, Qamar Uddin; Ming, Long Chiau; Mohamed, Nornisah (A and V Publication, 2017)
The kappa opioid receptor (KOR) system has been linked to many types of drug addiction. An upregulation of the KOR leads to negative reinforcement effects which might contribute to drug relapse. Previously, our study has shown that a treatment combination of 0.3 mg/kg buprenorphine and 1.0 mg/kg methamphetamine (a partial nociceptin opioid peptide [NOP] agonist and mu/kappa antagonists) has successfully attenuated relapse in morphine/methamphetamine (poly-drug)-dependent mice using a conditioned place preference (CPP) model. Therefore, this recent research work aimed to further investigate the involvement of the KOR system in poly-drug relapse at the brain level. The CPP test procedure was repeated where the mice were conditioned with poly-drug (7.5 mg/kg morphine and 1.0 mg/kg methamphetamine). Following CPP test, the investigation was extended at the brain level by using an immunohistochemistry (IHC) technique. Rabbit monoclonal (EPR 18881) was used as it will bind specifically at the KOR. The level of the KOR is determined at two different stages of addiction; the post-conditioning (dependence) phase and reinstatement (relapse) phase. Four brain regions that have high expression of the KOR and involved in addiction circuits have been selected to be investigated. A significant increment of the KOR expression was seen in striatum during reinstatement compared to post-conditioning (33.39 ± 5.60 % and 16.73 ± 5.27 % respectively, p < 0.05, n = 12). While a significant reduction of the KOR expression during reinstatement compared to post-conditioning observed in the prefrontal cortex (35.07 ± 3.51 % and 44.09 ± 1.78 respectively, p < 0.01, n = 12), no significant changes were detected in hippocampus and amygdala. Surprisingly, the KOR was not affected in amygdala which regulates emotion. The KOR upregulation seen in the striatum suggests that this brain region might be triggered in order to oppose the stimulus-related reaction caused by this poly-drug.